BOSHLANG’ICH SINF O’QUVCHILARIDA EKOLOGIK MADANIYATNI FANLARARO SHAKLLANTIRISH PEDAGOGIK MUAMMO SIFATIDA - Muxtarova, L.A. (SCIENCE and SOCIETY, 2021)
The article scientifically and theoretically describes the content of interdisciplinary environmental education of schoolchildren in the process of environmental education, forms of environmental education, methods of effective use of educational materials that provide interdisciplinary environmental education. At the same time, interdisciplinary integration helps students understand specification of the problems of forming a culture of environmental safety, the possibilities and problems of modern scientific and technological progress, ways of rational use of nature, the principles of a healthy lifestyle and the foundations of environmental safety.
Keywords: danger; safety; ecological culture; nature; life; environment; human; improvement of ecological control system; environmental protection